Analisis Kualitas Layanan E-Government Dispendukcapil Surabaya Menggunakan E-GovQual dan Importance Performance Analysis - Indira Setia Amalia; Clariza Risanti; Rivaldo Hadi Winata; Helmy Kurniawan (Journal Of Information System And Artificial Intelligence, 2022)
The use of E-Government became one of the utilization of information and communication technology as a support of government administration to improve the effectiveness, efficiency, accountability, and transparency of government and improve public services. One of the public services that is often encountered is about population. Surabaya City is one of the cities that implements E-Government in population and civil registration matters. E-Government services in the form of the Surabaya Dispendukcapil website will be measured using the E-GovQual method and Importance Performance Analysis to measure service quality and determine the service quality of the Surabaya Dispendukcapil. Result from this research shows the value of the level of conformity is 79.04% it is means that Surabaya Dispendukcapil still cannot meet user expectation with the results of the quadrant on the IPA showing the main priority on the design attribute (CAI4) and the search attribute (EU2).